DINAMIKA URBAN HEAT ISLAND DI KOTA PEKANBARU TAHUN 2013-2021 - Nugroho, Fadjar Iman; Adistio, M. Farry; Aaron Mambu, Dwight Viosela; Nouri, Mh. Nateq; Musyary, Muhammad Daffa (Jurnal Spasial, 2025)
Land clearing into built-up areas can cause the urban heat island phenomenon which can have an impact on microclimate change, especially in urban areas. This study aims to determine the effect of land cover dynamics, vegetation density (NDVI), and buildings (NDBI) on surface temperature in Pekanbaru City in 2013-2021, based on interpretation of Landsat 8 imagery in 2013 and 2021. Supervised classification-maximum likelihood analysis was used to identify land cover, and calculation of pixel values to identify temperature conditions, vegetation density index, and buildings using ENVI 5.3 and ArcGIS 10.5 software. Furthermore, multinomial logistic regression analysis was conducted using SPSS 25 software between the variables of land cover classification, vegetation density and buildings on land surface temperature to determine the factors that significantly affect the Urban Heat Island phenomenon in Pekanbaru City. The results of this study indicate that there is a relationship between land cover change and temperature increase in Pekanbaru City with a sig. value of <0.05. This indication is related to the increase in settlement area of 2,263 ha causing an increase in high temperature class (29-330C) which is spatially concentrated in Pekanbaru City.